Prioritizing health promotion lifestyle domains in students of Qazvin University of Medical Sciences from the students and professors' perspective - Pouresmaeil, Mahnaz (J Educ Health Promot, 2019)
INTRODUCTION: An individual's lifestyle is closely related to the health so that a healthy lifestyle improves the purpose of this study was prioritizing health promotion lifestyle domains in students of Qazvin University of Medical Sciences from the students and professors' perspective. MATERIALS AND METHODS: This study was done in cross-sectional method. The statistical population of this study consisted of students in Qazvin University of Medical Sciences in the academic year 2018. In addition, 10 faculty members in this university and five students were questioned in Delphi method from different educational groups. The questionnaire was used consisted of two parts. The first part included demographic characteristics, and the second part included the standard questions for Pender's health promotion model. The Delphi needs assessment method was also used to collect the information. RESULTS: The mean score of students' health-promoting behaviors was average (135.22 ± 19.35). The greatest score of health promotion behaviors was related to the spiritual growth scale (25.3 ± 5.4), and the lowest score was for physical activity (19.7 ± 05.1). The results of the Delphi method also suggested that both groups of faculty members and students believe that the dimensions of health accountability, physical activity, and prevention of high-risk behaviors in the students' lifestyle, need to be intervened. CONCLUSION: The results of the present study indicated that the students' lifestyle at Qazvin University of Medical Sciences was in average condition and low scores in the dimension of physical activity. Planned interventions should be made to promote health-promoting lifestyle among these students.